Proteoliposomes from mycobacterium bovis BCG and mycobacterium smegmatis as new vaccine candidates against tuberculosis - Kadir, Ramlah (2016)
Tuberculosis (TB) is caused by Mycobacterium tuberculosis (Mtb). It is an infection that can be fatal and one of the leading causes of death and illness in the world. The bacteria typi cally attack the lungs, but can also attack other parts of the body such brain, kidney and spine. Bacille Calmette-Gúerin (BCG) is the world‘s most widely used vaccine and is the only vaccine available against TB. Studies show that BCG can protect against, or at least ameliorate, severe forms of systemic TB in children, particularly meningitis. Nevertheless, it seems to be of low or no protective value against pulmonary TB in adults. Thus, candidate vaccines more potent than BCG are desperately needed to protect against TB disease and transmission. Considering the genomic and antigenic homology between Mtb and non-pathogenic BCG and Mycobacterium smegmatis (Ms), we decided to evaluate the potential of proteoliposomes (PLs) from BCG and Ms as vaccine candidates against TB. Bioinformatics studies predicted the presence of T and B cell epitopes in PLs from BCG and Ms which are expressed in vivo by Mtb during infection. Determination of human leukocyte antigen (HLA) have shown these epitopes provide the best percentage in the population of Malay and Cuba. Therefore, PLs from BCG (PLBCG) and Ms (PLMs) were prepared to evaluate the immunogenicity and crossreactivity with Mtb antigens. These PLs were confirmed to be spherical and homogenous in their size and shape under electron microscopy and chromatographic study. We subsequently, evaluated the antigenicity of PLBCG and PLMs in humans. We showed that healthy individuals produced IFN-γ in the presence of PLs which could be explained due to BCG vaccination and contact with environmental mycobacteria. In contrast, the lower response of IFN- of TB patients could be explained by immunodepression and genetic factors/susceptability. In addition, ELISA and Western blot analyses showed that the PLs are recognized by sera from TB patients, which suggested the presence of Mtb antigens expressed in vivo during active infection in PLBCG and PLMs. Animal studies demonstrated that immunization with PLBCG adjuvanted with alum (AL) induced a specific humoral immune response with elicitation of a mixed Th1/ Th2 pattern and stimulation of specific cellular immune response in vivo with positive delayed type hypersensitivity (DTH) response against PLBCG. Immunization with PLBCG combined with Montanide ISA 51 VG (MT) elicited a humoral Th2 immune response against PLBCG. Mice immunized with PLMs adjuvanted with AL showed a specific antibody response against PLMs with elicitation of Th2 pattern. Splenocytes from PLMs- immunized mice produced a Th2 pattern of cytokine response in vitro against PLMs. Mice immunized with both PLBCG and PLMs adjuvanted with AL and PLBCG with MT induced a humoral cross-reactive response against Mtb antigens with elicitation of a Th2 pattern but failed to produce cytokine response against Mtb antigens. Mice immunized with PLMs adjuvanted with AL produced cellular crossreactive responses in vivo with significant increase of DTH response against whole cell lysate from Mtb (Mtb-WCL). The pattern of recognition of proteins from PLs and Mtb by immunized animals differs depending of the adjuvant used. In conclusion, the results obtained in the current study support the future evaluation of the protective capability of these formulations in challenge experiments with Mtb in animal models.